ACCURACY OF POSTERIORANTERIOR THORACIC PHOTOGRAPHY IN DETERMINING CARDIOMEGALY AND CHAMBER ENLARGEMENT COMPARED TO ECHOCARDIOGRAPHY AT THE HAJI ADAM MALIK CENTRAL GENERAL HOSPITAL MEDAN YEAR 2023 - Tri Widi Wibowo; Henny Maisara Sipahutar; Hilfan Ade Putra Lubis (MEDALION JOURNAL: Medical Research, Nursing, Health and Midwife Participation, 2024)
Background: The main modality for identifying cardiac chamber enlargement is echocardiography examination, but due to its limitations, posteroanterior (PA) chest X-ray is often used as an alternative method. Methods: This study is an observational study with a cross-sectional design conducted at Radiology Installation and Polyclinic of Integrated Heart Center of The Haji Adam Malik Central General Hospital in patients who came to cardiac polyclinic or emergency room of Integrated Heart Center of The Haji Adam Malik Central General Hospital and underwent posteroanterior chest X-ray and echocardiography who met the inclusion and exclusion criteria. Data were analyzed descriptively to determine the frequency distribution of each demographic variable and risk factor. In addition, the level of sensitivity, specificity, positive predictive value, negative predictive value, of PA chest X-ray to echocardiography in patients with heart problems was calculated. Results: The sensitivity of PA chest X-ray for LVH examination was 91.8% with a specificity of 84.6% and accuracy of 89%; for RVH examination was 90.9% with a specificity of 68.2% and accuracy of 85%; for LAH examination was 89.2% with a specificity of 74.3% and accuracy of 84%; and for RAH examination was 70.4% with a specificity of 86.3% and accuracy of 82%. Conclusion: PA chest X-ray examination showed good accuracy for identifying cardiomegaly and cardiac chamber enlargement, therefore can be used as an alternative method besides echocardiography examination.